EFFECT OF THE USE OF MEDICAL MASK WASTE AS AN INGREDIENT IN LASTON AC-BC MIXTURE TO THE VALUE OF STABILITY - bobby damara (AGREGAT, 2023)
The construction of  highway construction is experiencing  a very rapid development  , especially in  Indonesia and  it is undeniable  that highways  are a  vital  sector of economic development in developed countries,  Realizing the importance of toll roads for logistics delivery, the government continued to speed up its construction starting in 2015(Afriyanto, Indriyati and Hardini, 2019). Until 2018, the toll road that has been built along 782 Km. Development continues to date, the government targets the construction of toll roads in 2019 along 1,070 Km. Total toll road construction later, during the reign of President Jokowi reached 1,852 Km (Ariswa, Andriani and Irawan, 2020)The COVID-19 pandemic is  a very disturbing outbreak for  Indonesian  citizens and  for the  world since the  beginning of the emergence of covid-19 in our country  is required to adapt  by implementing 3M (social distancing, wearing masks, and washing hands)(Wang et al., 2022),  the use of masks has become mandatory  in this  pandemic  masses and due to overload  the use of masks, especially 3 ply medical   masks made of water-absorbing materials such as cotton on the final layer  then the middle layer as a filter is made of materials such as non-woven polypropylene and  the outer layer is made of waterproof materials such as  polyester, in accordance with WHO advice  the use of masks is required as an effort to break the  chain of  the covid-19 virus so that  it does not spread widely but  As a result of the use of  masks with a high amount  ,   of course, there is an effect on the environment that masks  cannot be decomposed   properly by  the soil because physically the masks  have Plastic-like characters   are plastic that takes  a long time to decompose with soil(Dong et al., 2021).Seeing the   problem of medical mask  waste p there is this new normal era,  we are required to always innovate in  order  to  adapt to  the Covid-19 pandemic, in line with the leadership of  President Jokowidodo who carries  the  advancement of infrastructure in  Indonesia, especially in the   highway sector,  this study aims to utilize medical mask  waste as a hot asphalt  mixture material (Asphalt Hotmix)  by using  the experimental method of  using  waste masks with a composition of 5%, 7% and 10% as a  substitute for  asphalt which is reviewed on  asphalt stability